Cross Cultural Analysis of Direct Employee Participation: Dealing With Gender and Cultural Values - Valverde-Moreno, Marta; Torres-Jiménez, Mercedes; Lucia-Casademunt, Ana M.; Muñoz-Ocaña, Yolanda (Frontiers in Psychology, 2019)
The goal of this study is analyse the influence of perceived supervisor support (PSS) by employees at a micro level and the role of the cultural values of “power distance” and “masculinity” at a macro level on direct employee participation in decision making (PDM). Furthermore, the influence of the gender of managers and employees is taken into account. The analysis is based upon the Sixth European Working Conditions Survey carried out by Eurofound in 2016. The results of a Hierarchical linear model indicate that all predictors significantly influenced PDM and PSS positively and cultural values negatively. When the gender of managers and employees is considered, the findings suggest that PSS has a larger impact on PDM when male managers address female employees. Regarding the moderating effect of PSS on cultural values, it is shown that masculinity and power distance lose importance when employees have the support of their supervisors.